Mutations in TPM3 are a common cause of congenital fiber type disproportion - Clarke, N.; Kolski, H.; Dye, Danielle; Lim, E.; Smith, R.; Patel, R.; Fahey, M.; Bellance, R.; Romero, N.; Johnson, E.; Labarre-Vila, A.; Monnier, N.; et al. (John Wiley and Son, 2008)
Objective: Congenital fiber type disproportion (CFTD) is a rare form of congenital myopathy in which the principal histological abnormality is hypotrophy of type 1 (slow-twitch) fibers compared with type 2 (fast-twitch) fibers. To date, mutation of ACTA1 and SEPN1 has been associated with CFTD, but the genetic basis in most patients is unclear. The gene encoding a-tropomyosinslow (TPM3) is a rare cause of nemaline myopathy, previously reported in only five families. We investigated whether mutation of TPM3 is a cause of CFTD. Methods and Results: We sequenced TPM3 in 23 unrelated probands with CFTD or CFTD-like presentations of unknown cause and identified novel heterozygous missense mutations in five CFTD families (p. Leu100Met, p.Arg168Cys, p.Arg168Gly, p.Lys169Glu, p.Arg245Gly). All affected family members that underwent biopsy had typical histological features of CFTD, with type 1 fibers, on average, at least 50% smaller than type 2 fibers. We also report a sixth family in which a recurrent TPM3 mutation (p.Arg168His) was associated with histological features of CFTD and nemaline myopathy in different family members. We describe the clinical features of 11 affected patients. Typically, there was proximal limb girdle weakness, prominent weakness of neck flexion and ankle dorsiflexion, mild facial weakness, and mild ptosis. The age of onset and severity varied, even within the same family. Many patients required nocturnal noninvasive ventilation despite remaining ambulant. Interpretation: Mutation of TPM3 is the most common cause of CFTD reported to date. © 2008 American Neurological Association. Published by Wiley-Liss, Inc.